Levels of resilience, anxiety and depression in nurses working in respiratory clinical areas during the COVID pandemic. (January 2021) - Roberts, N.J.; McAloney-Kocaman, K.; Lippiett, K.; Ray, E.; Welch, L.; Kelly, C.
Abstract: Background: The delivery of healthcare during the COVID pandemic has had a significant impact on front line staff. Nurses who work with respiratory patients have been at the forefront of the pandemic response. Lessons can be learnt from these nurses' experiences in order to support these nurses during the existing pandemic and retain and mobilise this skilled workforce for future pandemics. Methods: This study explores UK nurses' experiences of working in a respiratory environment during the COVID-19 pandemic. An e-survey was distributed via professional respiratory societies; the survey included a resilience scale, the GAD7 (anxiety) and the PHQ9 (depression) tools. Demographic data was collected on age, gender, ethnicity, nursing experience and background, clinical role in the pandemic, and home-life and work balance. Results: Two hundred and fifty-five responses were received for the survey, predominately women (89%, 226/255), aged over 35 (79%, 202/255). Nearly 21% (40/191) experiencing moderate to severe or severe symptoms of anxiety. Similar levels are seen for depression (17.2%, 31/181). 18.9% (34/180) had a low or very low resilience score. Regression analysis showed that for both depression and anxiety variables, age and years of qualification provided the best model fit. Younger nurses with less experience have higher levels of anxiety and depression and had lower resilience. Conclusion: This cohort experienced significant levels of anxiety and depression, with moderate to high levels of resilience. Support mechanisms and interventions need to be put in place to support all nurses during pandemic outbreaks, particularly younger or less experienced staff. Highlights: There has been a mental health and psychological impact on the NHS workforce during the pandemic. This study has shown significant levels of anxiety and depression, with moderate to high levels of resilience. Support mechanisms and interventions are needed, particularly for younger or less experienced staff.